Cause Analysis of an Infection in Facelift Surgery Due to Mycobacterium chelonae - Decalonne, Marie; Lecorche, Emmanuel; Hau, Estelle; Petiteau, Agnès; Moreau, Célia; Milan, Odile; Lanotte, Philipe; Mereghetti, Laurent; Cambau, Emmanuelle; van der Mee-Marquet, Nathalie (Frontiers in Medicine, 2019)
We report a post-facelift infection due to Mycobacterium chelonae. An environmental strain recovered from the water supply network of the surgical clinic and the clinical strains were considered non-differentiable using whole genome sequencing. After the unhealed wound's exposure to M. chelonae while showering early at the clinic after surgery, a lasting exposure of the colonized wound to the warm and moist working conditions of a bakery may have been favorable to the infection's development.